Induced community tolerance of periphyton towards combined salt and toxic stress. (18th July 2016) - Schmitt‐Jansen, Mechthild; Bley, Lisa‐Marie; Krumbiegel, Marie‐Luise; Rotter, Stefanie
Summary: Aquatic ecosystems are exposed to multiple stressors requiring better integration of distinct disciplines such as ecotoxicology and ecology. Stressors select for increasing community tolerance which can be evidenced by the concept of 'pollution‐induced community tolerance' (PICT). However, for analysing combined stressor effects on community tolerance, suitable metabolic tests are needed. Salinisation and toxic exposure often co‐occur in aquatic systems. We aimed to develop a metabolic test to quantify salt tolerance by using proline as an indicator. This method was applied in microcosms, exposing periphyton to salt and an herbicide, individually and in combination. Proline was a suitable marker for salt stress in periphyton. Long‐term exposure to single stressors resulted in toxicant‐ and salt‐induced community tolerance, but not in co‐tolerances between the stressors. Induction ratios of proline suggest that proline may have different protective functions in organisms depending on stressor quality and resulting in contrasting tolerance patterns in periphyton. Biochemical markers provide a set of metabolic tests needed for a broader application of the PICT approach in ecology and ecotoxicology, especially for analysing combined stress. Induced community tolerance may therewith improve ecological relevance in environmental risk assessment of toxicants.